A Safe Education for All: Recognizing and Stemming Harassment in Music Classes and Ensembles - Carter, Bruce Allen (Music Educators Journal, 2011)
This article addresses the pervasiveness of harassment in schools in the United States and presents ways to recognize and stem bullying in music classrooms. Music educators are in a unique position to recognize atypical behaviors in their students. Music educators who teach middle and high school ensembles often retain the same students in their classrooms over the course of many years. Because of the unique nature of the ensemble experience, coupled with the opportunity for extended instruction, music teachers can closely monitor the well-being of their students. However, music teachers should understand how difficult it may be for students who have been harassed to come forward with information about harassment. Sometimes harassment is overt and easy to recognize (e.g., name-calling, inappropriate gestures, graffiti). However, harassment can also occur in contexts that are not readily recognized but are just as hurtful. When students observe teachers taking a stand against bullying and harassment, they recognize the intention for a safe classroom. When students feel safe, they are more likely to ask questions and engage in class in dynamic and meaningful ways—both musically and nonmusically. Only when students feel safe can they learn. Music teachers need to gain a further understanding of various forms of harassment and further consider their role in creating a welcoming and secure environment.
Keywords: Bullying; Harassment; Music classrooms; Myriam

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - G&#252, Hasan; rkan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Myriam; Turkey; film industry; gender; gender role; women

Indian women journalists' responses to sexism and sexual harassment - Chadha, Kalyani; Steiner, Linda; Guha, Pallavi (International Communication Research Journal, 2017)
Gale Academic OneFile includes Indian women journalists' responses to sexism and by Kalyani Chadha, Linda Steiner, and Pall. Click to explore.
Keywords: Myriam; journalism

Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Arts; Myriam; admiration; condonation; epistemic injustice; honor; silencing

Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate

Dick pics on blast: A woman’s resistance to online sexual harassment using humour, art and Instagram - Vitis, Laura; Gilmour, Fairleigh (Crime, Media, Culture, 2017)
This article brings to attention and explores women?s use of non-traditional forms of resistance to online sexual harassment. In this piece we use Anna Gensler?s Instagram art project Instagranniepants to examine how women are appropriating the language and practices of the cyber realm to expose online sexual harassment and to engender a creative resistance which is critical, comedic and entertaining. Drawing from interdisciplinary literature on witnessing, satire and shaming, we explore the techniques Gensler uses to not only document harassment but also resist, engage and punish those who seek to perpetrate it. This article problematises the stereotype of women as passive victims of online public spaces, and is critical of popular discourses that portray online spaces as exclusively risky and that position women as the natural victims of online violence. It concludes that a more nuanced account of women?s negotiation of online spaces is necessary, particularly as an overarching narrative of risk and victimisation undermines the liberatory potential of the online realm.
Keywords: Myriam; Résistance aux VACS